Archetypal images in the novel “Nakanune” by I.S. Turgenev (Eurasian Journal of Philology Science and Education, 2022)
This article examines the archetypal images in the novel “Nakanune” (“On the Eve”) by I. S. Turgenev. For a detailed analysis of them, it was necessary to study the poetics of the novel’s title, the semantics of the characters’ images, the functions of archetypes and mythologems in work. Myths can be perceived as literature itself and as historical sources for subsequent creation of literary works. Some scientists regard such literary works as reworked myths. In the days of the Stoics and Epicureans, mythical stories were understood as allegories. The people, not being able to explain various phenomena, endowed them with their own properties. People perceived obscure, magical, strange phenomena as real, valid, and explained all this with ordinary human logic. And they perceived myths as allegory. The interest in myths at the beginning of the twentieth century lies in human consciousness and interest in the topic: what our life is. And although the myth can sometimes be opposed to modernity, but it is he who allows us today to understand modern human life. Myths contain history, distorted facts, and experience, based on which we can develop our consciousness and build our lives. The relevance of the article lies in the need for a detailed study of the mythopoetics of the novel by I. S. Turgenev “Nakanune” from new methodological positions, namely, in the aspect of the mythopoetic approach. It allows using methods of analyzing mythopoetics and considering the archetypes of character images, symbols and other details transmitted by the author with the help of mythologemes. We tried not only to give the comments about mythological images of this novel, but also to study their aesthetic functions, and we tried explore the archetypal nature of the images and motives of the work together. For this work we used mythopoetic, semiotic, comparative and other methods. Key words: mythopoetics of the novel, mythological subtext, archetypal images, mythological symbols, functions of mythologems.